2020
DOI: 10.1002/nau.24389
|View full text |Cite
|
Sign up to set email alerts
|

Early 3‐month treatment with comprehensive physical therapy program restores continence in urinary incontinence patients after radical prostatectomy: A randomized controlled trial

Abstract: Aims The objective of this study is to ascertain whether an early three‐month treatment with electrotherapy and biofeedback restores continence in urinary incontinence patients after radical prostatectomy (RP). Methods Design: The study performed a randomized, controlled trial of parallel and open groups. Configuration: Secondary care, urology department of a university hospital complex. Participants: Patients sent for RP due to prostate cancer (n = 60), 47 patients finally completed the study. Interventions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 38 publications
0
13
0
5
Order By: Relevance
“…To the best of the authors′ knowledge, this is the first study analyzing the contraction of the abdominal muscles during HE in both sexes and considering sex differences. Up to now, the benefits of HE have been studied and described in women with pelvic floor or abdominal dysfunctions; however, the results presented in this study provide for the first time information about the activation of the abdominal muscles in men during HE, and support their use in several situations, such as urinary incontinence after prostatectomy or pelvic floor muscles′ dysfunctions, where men and women need similar treatments, but from different perspectives, according to their anatomy and also to the activation of their muscles [ 12 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…To the best of the authors′ knowledge, this is the first study analyzing the contraction of the abdominal muscles during HE in both sexes and considering sex differences. Up to now, the benefits of HE have been studied and described in women with pelvic floor or abdominal dysfunctions; however, the results presented in this study provide for the first time information about the activation of the abdominal muscles in men during HE, and support their use in several situations, such as urinary incontinence after prostatectomy or pelvic floor muscles′ dysfunctions, where men and women need similar treatments, but from different perspectives, according to their anatomy and also to the activation of their muscles [ 12 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 80%
“…These exercises are demonstrated to decrease intraabdominal pressure and activate the pelvic floor muscles and the abdominal wall, and thus, they are designed for the prevention and treatment of perineal dysfunctions, especially in postpartum [ 1 ]. Consequently, HE are mainly performed by women, with benefits in pelvic floor dysfunctions or urinary incontinence [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], but recently new scientific research has demonstrated that men with urinary incontinence, scoliosis, or low back pain could also be benefited from these exercises [ 9 , 10 , 11 , 12 ]. Other studies have shown that HE could induce changes in postural muscles, such as increases in muscle thickness, cross-sectional area, or length [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the analyzed research protocols, electrostimulation was combined with other PFM therapeutic techniques [ 16 , 27 , 30 , 33 , 40 , 48 , 52 ] and lasted between 15 [ 16 , 31 , 40 , 52 ] and 20 min [ 27 , 33 , 34 ]. Ahmed et al [ 16 ] observed that UI therapy outcomes may improve after combining ES therapy with BF [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous researches have put effort into identifying factors affecting post‐operative LUTS in patients with PC, which generally include radiation therapy, body mass index (BMI), age, prostate‐specific antigen (PSA) level and post‐operative physical therapy (Khoder et al, 2013 ; Matsukawa et al, 2020 ; Soto González et al, 2020 ). However, few have looked into the effect of nursing intervention, which in fact carries substantial weight for patient quality of life.…”
Section: Introductionmentioning
confidence: 99%